2013
DOI: 10.5600/mmrr.003.03.a05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-term Care Use on Medicare and Medicaid Expenditures for Dual Eligible and Non-dual Eligible Elderly Beneficiaries

Abstract: Results: Among dual eligibles and non-dual eligibles, the average number of diseases and case mix scores are higher for LTC users. Adjusting for case mix virtually eliminates the difference for medical costs, but not for LTC expenditures. Adjusting for LTC status reduces the difference in LTC costs, but increases the difference in medical costs. Conclusions:Efforts to control costs for dual eligibles should target those in LTC while better coordinating medical and LTC expenditures. Access, Demand Uninsured, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Unlike the findings of Wysocki et al 9 and Kane et al, 10 we did not find that the higher cost for LTSS provided in nursing facilities was fully offset by lower acute and postacute spending when compared with those receiving LTSS in the community. However, we did observe in our multivariate analysis that older age and cognitive limitations were associated with higher LTSS spending and lower acute and postacute expenditures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the findings of Wysocki et al 9 and Kane et al, 10 we did not find that the higher cost for LTSS provided in nursing facilities was fully offset by lower acute and postacute spending when compared with those receiving LTSS in the community. However, we did observe in our multivariate analysis that older age and cognitive limitations were associated with higher LTSS spending and lower acute and postacute expenditures.…”
Section: Discussioncontrasting
confidence: 99%
“…8 However, others have found that nursing facility care may be offset by lower spending in acute and postacute settings, especially among individuals with complex health needs. 9,10 In the current study, we attempted to unravel the contribution of individual health factors from delivery system factors to determine the source of expenses for California MMEs who initiated either extended nursing facility care or HCBS. We applied propensity score methods to construct samples of MMEs with similar levels of need using each type of LTSS.…”
mentioning
confidence: 99%
“…A possible explanation for this finding is that RNs may not be equipped with the assessment and treatment skills or practice jurisdiction necessary to independently treat certain health conditions, and thus opt to transfer them to the ED. While our findings support the argument that the use of NPs in LTC homes reduces the need for acute care and ED services (Kane, Keckhafer, Flood, Bershadsky, & Siadaty, 2003;Klaasen et al, 2009), we believe that our study is unique in that it is likely the first to compare ED transfer across NPs, MDs, and RNs using adjusted GEE analyses.…”
Section: Np-led Outreach Program For Ltc Homessupporting
confidence: 74%
“…Beginning in 2001, the Centers for Medicare and Medicaid Services (CMS) awarded states and other organizations with Real Choice System Changes grants to encourage the infrastructure needed to support HCBS by creating a capacity for personal attendant services, developing NH transition programs, establishing Aging and Disability Resource Centers to provide better information for consumers, and developing quality management in HCBS. From 2003 to 2005, with CMS funding, we used mixed methods to study the rebalancing experience in eight states …”
Section: Social and Policy Backdrop For Evolution Of Ltcmentioning
confidence: 99%
“…From 2003 to 2005, with CMS funding, we used mixed methods to study the rebalancing experience in eight states. 40 We have consistently tried to advance quality. From 1998 to 2002, under a CMS contract, we developed and tested measures of NHs residents' QOL, collecting the data directly from residents-even those with substantial cognitive impairment.…”
Section: Social and Policy Backdrop For Evolution Of Ltcmentioning
confidence: 99%